1994
DOI: 10.1055/s-2006-959500
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Components Isolated from the Chinese Herbal MedicineCoix lachryma-jobi

Abstract: The seeds of the gramineous plant Coix lachryma-jobi L. var. ma-yuen Stapf are a traditional Chinese medicine possessing antitumor activity. An acetone extract of the seeds was fractionated by the aqueous alkali method and by silica gel column chromatography in order to identify the antitumor components. Antitumor activity, as assayed by an in vivo growth inhibition test on a transplantable mouse tumor, was attributed to an acidic fraction. Infrared spectroscopy and gas-liquid chromatography showed that this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 2 publications
1
39
0
Order By: Relevance
“…ma-yuen stapf), a close relative of oats, has been thought to have health benefits, but there has been a lack of scientific studies to support this notion. Recent studies, however, indicate that adlay may possess diuretic, anticonvulsant, and antitumor activities 7,8) and may be effective in decreasing plasma cholesterol and triacylglycerol (TG) and in increasing high-density lipoprotein-cholesterol (HDL-C).…”
mentioning
confidence: 99%
“…ma-yuen stapf), a close relative of oats, has been thought to have health benefits, but there has been a lack of scientific studies to support this notion. Recent studies, however, indicate that adlay may possess diuretic, anticonvulsant, and antitumor activities 7,8) and may be effective in decreasing plasma cholesterol and triacylglycerol (TG) and in increasing high-density lipoprotein-cholesterol (HDL-C).…”
mentioning
confidence: 99%
“…At all temperatures, linoleic acid contents in S5 and S5L were decreased in time-dependent pattern with the maximum percentage remaining of linoleic acid at 4 C. The anticancer activity of the liposome formulation might be due to the linoleic acid in S5. Linoleic acid was the major fatty acid in Job's tear seed (Bhandari et al, 2014), which inhibited the growth of mouse tumor transplant (Numata et al, 1994) and induced apoptosis by mitochondrial dysfunction induction in cancer cell (Lu et al, 2010). At the end of the experiment, the linoleic acid contents of S5L were higher than nonencapsulated S5.…”
Section: Linoleic Acid Content In the Free And Semi-purified Job's Tementioning
confidence: 99%
“…Phytochemistry studies revealed the presence of phytosterols, phenolic acids, phenolic aldehydes, lignan and flavonoids in adlay bran extract. 3,7,10,49 We have isolated some isoflavone and flavonoid phytochemicals in adlay bran extracts (unpublished data). Flavonoid phytochemicals have been shown to possess an inhibitory effect on steroidogenic enzymes in human adrenocortical H295R cells.…”
Section: Downregulation Of Progesterone Biosynthesis By Abm S-m Hsia mentioning
confidence: 99%
“…2 Adlay extracts inhibit growth of Ehrlich ascites sarcoma and their active components have been identified as coixenolides. 3 The adlay extracts have been studied to be antiproliferative and chemopreventive on lung or colon cancer in vivo and in vitro. [4][5][6] Methanolic extracts from adlay seeds have been reported to have a moderate antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%